RSM Analysis for Optimum Content of Graphene Nanoplatelets for 3D-Printed Clay Strength - Mohsen, Mohamed; Al-Diseet, Malak; Abu Rumman, Mervat; Taha, Ramzi; Naji, Khalid (Proceedings of the International Conference on Civil Infrastructure and Construction (CIC), 2023)
This study applies Response Surface Methodologies (RSM) methods to maximize 3D-Printed clay mechanical properties. Mixes containing different Graphene Nanoplatelets (GNPs) contents were printed and tested in compression and flexure. The Central Composite Design method was used by coding the mixes fabrication method, i.e. moulding and printing, and GNPs content as variables. The analysis showed that the mixes containing low GNPs content of 0.1 wt.% attained higher compressive and flexural strengths than those containing a higher content of 0.2 and 0.3 wt.%. The results also highlighted that GNPs' efficiency was better observed in the printed samples other than the moulded ones, indicating that the printing process contributed to a better and uniform dispersion of GNPs in the clay matrix. RSM analysis confirmed that the maximum flexural strength response could be obtained using a GNPs content of 0.1 wt.%. Furthermore, the desirability analysis showed that a maximum predicted flexural and compressive strength improvements of 21% and 36 % compared to the control mixes could be obtained, respectively. In summary, this study proposed the importance of using Nanofilaments in 3D printing activities to achieve the desired elements' mechanical properties.